The Use of Incentive Compensation Among Board Members in Family Firms. (April 2014) - Muñoz-Bullón, Fernando; Sánchez-Bueno, María J.
Although previous literature has focused on managerial compensation differences between family and non-family firms, the examination of differences in the compensation structure of family directors versus their non-family counterparts within family firms has received much less attention. We analyze several contingencies related to directors' kinship ties to the owning family that may influence directors' total compensation levels and their incentive compensation in family firms. The empirical evidence is provided by a sample of publicly listed family firms from the United States. Our results show that family-member directors receive a lower share of variable pay and a lower level of total compensation than non-family directors within the same firm. In addition, a high family ownership concentration and a large proportion of family members on the board impact negatively on the use of incentive compensation among board members with kinship ties to the owning family.